Malignant adenomyoepithelioma of the breast with axillary lymph node metastasis: a case report and review of the literature - Wang, Wei; Chen, Long; Wen, Shaoji; Jiang, Jianzhong; Tang, Gang; Gao, Cheng; Wei, Binan; Zhou, Feiyu (Frontiers in Oncology, 2025)
BackgroundAdenomyoepithelioma (AME) is a relatively rare type of tumor formed by the coordinated proliferation of glandular epithelial cells and myoepithelial cells. Clinically, most of them are benign, while malignant ones are extremely rare. Malignant breast adenomyoepithelioma is somewhat invasive and may recur locally or metastasize distantly through the vascular pathway. However, reports on axillary lymph node metastasis are scarce. In this case, we present an extremely rare instance of malignant breast adenomyoepithelioma with axillary lymph node metastasis. By combining previous studies, we conduct an in-depth analysis of the clinicopathological features, treatment methods, and prognosis of this disease, and propose targeted diagnostic and treatment suggestions.Case presentationA 64-year-old woman initially presented with no abnormalities in the axillary lymph nodes upon clinical examination or imaging. Following the diagnosis of malignant adenomyoepithelioma, the patient underwent unilateral mastectomy. Six months after surgery, the patient developed ipsilateral axillary lymph node enlargement, which was confirmed by pathological examination as metastasis of malignant adenomyoepithelioma of the breast to the axillary lymph nodes. The patient underwent axillary lymph node dissection, followed by four cycles of epirubicin and cyclophosphamide (AC) chemotherapy. Nine months after the operation, the patient returned to our outpatient clinic for follow-up, and the examination results showed no signs of recurrence or distant metastasis.ConclusionWe meticulously described the clinical symptoms, signs, and imaging characteristics of both the primary lesion of malignant adenomyoepithelioma of the breast and its axillary metastasis in the patient. Through a comparison of the pathologic features between the primary breast lesion and the axillary metastatic lymph nodes, we found a certain degree of consistency in terms of microscopic pathologic features and immunohistochemical molecular expression. Furthermore, we conducted an extensive review of the literature on breast malignant adenomyoepithelioma over the past decade. By summarizing the clinicopathological characteristics, treatment modalities, and prognosis of the patients, we found that patients with breast malignant adenomyoepithelioma have a certain risk of recurrence and metastasis. Notably, even when the clinical examination of axillary lymph nodes yields negative results and imaging shows no enlargement, a more assertive surgical approach may still be necessary. Specifically, a sentinel lymph node biopsy, despite the potential for false-negative outcomes, could be advantageous for the patient’s prognosis by enabling early determination of the need for axillary lymph node dissection.